(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
This study evaluated Lophira lanceolata n-butanol leaf fraction hepatoprotective and antioxidant potentials in the Drosophila melanogaster model. For the acute toxicity study, adult Drosophila melanogaster were exposed to L. lanceolata butanol fraction at concentrations of 125, 250 and 500 mg/10g feed, and mortality was recorded for a period of seven days. In the hepatotoxicity assay, flies were fed the n-butanol fraction at 125, 250, and 500 mg/10g, with all the groups receiving carbon tetrachloride mixed with the feed, and antioxidant enzyme activities (catalase, superoxide dismutase, and reduced glutathione) were measured. In the oxidative stress assay similar dose pattern was adopted. The adult flies were homogenized, and biochemical assays for hepatic biomarkers and oxidative stress markers were evaluated. A sample of the Drosophila homogenate was subjected to mRNA extraction for the expression of the SOD gene. The LC50 was determined to be greater than or equal to 500 mg fraction in 10g of feed. Antioxidant enzyme activities (catalase, superoxide dismutase, and glutathione) significantly increased upon administration of the graded doses of L. lanceolata n-butanol fraction. The liver biochemical markers, such as ALT, AST, Albumin, and alkaline phosphatase, were significantly decreased by the n-butanol fraction compared with the CCl4-treated group. These results suggest that L. lanceolata possesses antioxidant and hepatoprotective effects on Drosophila flies by free radical scavenging and increasing gene expression of endogenous antioxidant enzymes.